Pre-theory design frameworks and design theorizing - Baskerville, Richard; Vaishnavi, V. (2016)
© 2016 IEEE.This paper advances the concept of pre-theory design frameworks as a notable means of justifying early design experiences that form preliminaries to design theories. Design work situated in complex design problem settings can field artifacts that shift the entropy in the setting (i.e., relocate work and noise). Such shifts can trigger a progressive transformation from a problem setting to a solution setting. Pre-theory design frameworks provide formative functional explanations that embody a starting point for theorizing in design science research. This progressive formulation and reformulation of concepts and constructs represents the progress of design science knowledge from lower to higher levels of abstraction. This explanation accounts for the apparent rationality of design theorizing in a messy, emergent design problem setting. The frameworks are elaborated in a dissipative structure model based on the varying level of entropy present in the design activities and the actions that cope with this entropy.